Atypical Squamous Cells of Undetermined Significance: Bethesda Classification and Association with Human Papillomavirus. (29th June 2011) - Barcelos, Ana Cristina Macêdo; Michelin, Márcia Antoniazi; Adad, Sheila Jorge; Murta, Eddie Fernando Candido
Abstract : Introduction . To analyze patients with atypical squamous cells of undetermined significance (ASCUS) through a cytology review and the presence of microbiological agents, with consideration of colposcopy and semiannual tracking. Methods . 103 women with ASCUS were reviewed and reclassified: normal/inflammatory, ASCUS, low-grade squamous intraepithelial lesion (LSIL), or high-grade squamous intraepithelial lesion (HSIL). If ASCUS confirmed, it was subclassified in reactive or neoplastic ASCUS, ASC-US, or ASC-H; and Regione Emilia Romagna Screening Protocol. Patients underwent a colposcopic examination, and test for Candida sp., bacterial vaginosis, Trichomonas vaginalis, and human papillomavirus (HPV) were performed. Results . Upon review, ASCUS was diagnosis in 70/103 (67.9%), being 38 (54.2%) reactive ASCUS and 32 (45.71%) neoplastic ASCUS; 62 (88.5%) ASC-US and 8 (11.41%) ASC-H. ASCUS (Regione Protocol), respectively 1-5: 15 (21.4%), 19 (27.1%), 3 (27.1%), 16 (22.8%), and 1 (1.4%). A higher number of cases of cervical intraepithelial neoplasia (CIN) II/III in the biopsies of patients with ASC-H compared to ASC-US (P = .0021 ). High-risk HPV test and presence of CIN II/III are more frequent in ASC-H than ASC-US (P = .031 ). Conclusions . ASC-H is associated with clinically significant disease. High-risk HPV-positive status in the triage for colposcopy of patients with ASC-US is associated with increased of CIN.